Genotype‐guided diagnostic reassessment after exome sequencing in neuromuscular disorders: experiences with a two‐step approach. (13th August 2019) - Krenn, M.; Tomschik, M.; Rath, J.; Cetin, H.; Grisold, A.; Zulehner, G.; Milenkovic, I.; Stogmann, E.; Zimprich, A.; Strom, T. M.; Meitinger, T.; Wagner, M.; et al.
Abstract : Background and purpose: Next‐generation sequencing has greatly improved the diagnostic success rates for genetic neuromuscular disorders (NMDs). Nevertheless, most patients still remain undiagnosed, and there is a need to maximize the diagnostic yield. Methods: A retrospective study was conducted on 72 patients with NMDs who underwent exome sequencing (ES), partly followed by genotype‐guided diagnostic reassessment and secondary investigations. The diagnostic yields that would have been achieved by appropriately chosen narrow and comprehensive gene panels were also analysed. Results: The initial diagnostic yield of ES was 30.6% ( n = 22/72 patients). In an additional 15.3% of patients ( n = 11/72) ES results were of unknown clinical significance. After genotype‐guided diagnostic reassessment and complementary investigations, the yield was increased to 37.5% ( n = 27/72). Compared to ES, targeted gene panels (<25 kilobases) reached a diagnostic yield of 22.2% ( n = 16/72), whereas comprehensive gene panels achieved 34.7% ( n = 25/72). Conclusion: Exome sequencing allows the detection of pathogenic variants missed by (narrowly) targeted gene panel approaches. Diagnostic reassessment after genetic testing further enhances the diagnostic outcomes for NMDs.